A two-dimensional hybrid model of the Hall thruster discharge - Parra, F; Ahedo, E; Fife, J; Martinez-Sanchez, M (2006)
Particle-in-cell methods are used for ions and neutrals. Probabilistic methods are implemented for ionization, charge-exchange collisions, gas injection, and particle-wall interaction. A diffusive macroscopic model is proposed for the strongly magnetized electron population. Cross-field electron transport includes wall collisionality and Bohm-type diffusion, the last one dominating in most of the discharge. Plasma quasineutrality applies except for space-charge sheaths, which are modeled taking into consideration secondary-electron-emission and space-charge saturation. Specific weighting algorithms are developed in order to fulfil the Bohm condition on the ion flow at the boundaries of the quasineutral domain. The consequence is the full development of the radial plasma structure and correct values for ion losses at lateral walls. The model gains in insight and physical consistency over a previous version, but thrust efficiency is lower than in experiments, indicating that further model refinement of some phenomena is necessary. © 2006 American Institute of Physics.